Study On Service Quality On Customer Satisfaction And Loyalty - Siti Fatimah; Mukhammad Idrus; Afiah Mukhtar; Karta Negara Salam; Ismawati Ismawati (Jurnal Manajemen, 2022)
This study investigates the impact of service quality on the satisfaction and loyalty of RSUD Andi Djemma Masamba inpatients. Quantitative causal studies are included in this type of research. The population of this study consisted of 14,501 inpatients at the Andi Djemma Masamba Hospital. However, only 150 samples were used because this quantity met the minimum number of samples required for SEM model testing. Primary data sources were used for this study. The collected data will be subjected to a series of tests, including descriptive analysis, a data quality test consisting of (validity and reliability tests), a classical assumption test consisting of a normality test and an outlier’s test, and a SEM analysis conducted with the AMOS program to test the hypothesis. According to the findings of this study, the quality of service has a direct and significant impact on the satisfaction of inpatients at the Andi Djemma Masamba Hospital. At the Andi Djemma Masamba Hospital, service quality has a significant positive direct and indirect effect on the loyalty of inpatients. The commitment of inpatients at the Andi Djemma Masamba Hospital is positively and immediately affected by their level of satisfaction.